2009
DOI: 10.1016/j.ijom.2009.03.436
|View full text |Cite
|
Sign up to set email alerts
|

Electrosonographic characteristics of sounds from temporomandibular joint disc replacement

Abstract: Free Papers-Oral Presentations 519induce chondrogenesis and osteogenesis to a basal medium. DCM coupled with supplemented growth factors was tested for its ability to differentiate BMSCs into osteogenic and chondrogenic lineages in two-dimensional (2D) and three-dimensional (3D) cultures. When transforming growth factor-beta3 was added into DCM, BMSCs differentiated to chondrocyte-like cells evidenced by the expression of glycosaminoglycan and type II collagen, whereas osteogenic differentiation was induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
4
0
5
Order By: Relevance
“…Other studies have identified the characteristic wave pattern of the joint vibration for each different TMD condition . Owen categorised five specific wave forms to describe the joint conditions: (i) joint inflammation was identified in the frequency pattern as a small spike in the 25 Hz range, (ii) Disc movement (DM) was defined as the early stages of internal problems occurring when the lateral collateral ligaments have become loosened or elongated allowing the disc to move.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have identified the characteristic wave pattern of the joint vibration for each different TMD condition . Owen categorised five specific wave forms to describe the joint conditions: (i) joint inflammation was identified in the frequency pattern as a small spike in the 25 Hz range, (ii) Disc movement (DM) was defined as the early stages of internal problems occurring when the lateral collateral ligaments have become loosened or elongated allowing the disc to move.…”
Section: Resultsmentioning
confidence: 99%
“…Temporomandibular disorders (TMD) have deserve considerable research since patients present clinical characteristics of limited mouth opening, masticatory muscle spasms, internal derangement in the joints, and consequent instability of the disc-condyle complex producing articular sounds. According some authors, intra-articular sounds are universally accepted signs of TMD and they have correlated types of vibrations with specific disorders (2), although these signs also manifest in asymptomatic subjects (3).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that TMJ sounds (clicking, tripping noises and crepitus) are indication of various clinical conditions (1,3,5,6). Some of these sounds indicate severe dysfunction needing immediate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A fim de minimizar a subjetividade na avaliação dos ruídos, diversos pesquisadores utilizaram métodos de gravação do som (Wakebe et al, 1994;Prinz, 1996;Bertolami, 1998;Leader et al, 2001;Tanzilli et al, 2001;Ogutcen-Toller , 2003; Widmalm et al, 2006;Deng et al, 2006;Garcia et al, 2008;Mazetto et al, 2009).…”
Section: Lista De Figurasunclassified
“…Para pesquisar e as características eletrosonograficas de sons originários de desarranjos intra-articulares, Deng et al (2006) (Motoyoshi et al,1994 ).…”
Section: Revisão Da Literaturaunclassified